1999
DOI: 10.1007/s002590050409
|View full text |Cite
|
Sign up to set email alerts
|

Respective roles of scatter, attenuation, depth-dependent collimator response and finite spatial resolution in cardiac single-photon emission tomography quantitation: a Monte Carlo study

Abstract: The purpose of this study was to investigate the relative influence of scatter, attenuation, depth-dependent collimator response and finite spatial resolution upon the image characteristics in cardiac single-photon emission tomography (SPET). An acquisition of an anthropomorphic cardiac phantom was performed together with corresponding SPET Monte Carlo simulations. The cardiac phantom and the Monte Carlo simulations were designed so that the effect of scatter, attenuation, depth-dependent collimator response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Then, compensation must be made for the efficiency of the detection device and for spatial variations in detection efficiency caused by losses of radiation due to absorption and Compton scattering in intervening tissues [el-Fakhri et al, 1999;Buvat et al, 1998Buvat et al, , 1995Miller et al, 1996;. Quantification by PET has been extensively validated [Rhodes and Hughes, 1995;Korf, 1997;Leskinen, 1994;Czernin and Schelbert, 1994;Kuwert et al, 1992].…”
Section: Quantification Issuesmentioning
confidence: 98%
See 1 more Smart Citation
“…Then, compensation must be made for the efficiency of the detection device and for spatial variations in detection efficiency caused by losses of radiation due to absorption and Compton scattering in intervening tissues [el-Fakhri et al, 1999;Buvat et al, 1998Buvat et al, , 1995Miller et al, 1996;. Quantification by PET has been extensively validated [Rhodes and Hughes, 1995;Korf, 1997;Leskinen, 1994;Czernin and Schelbert, 1994;Kuwert et al, 1992].…”
Section: Quantification Issuesmentioning
confidence: 98%
“…They are also important in qualitative imaging because of the large effect they have on perceived tracer distribution within the body (note that Figs. 4 and 5 are images of a single drug formulation in a single person), but they are rarely done using sufficiently rigorous methods for the type of data being analyzed [Buvat et al, 1995[Buvat et al, , 1998el-Fakhri et al, 1999;Perring et al, 1994;Lee et al, 1999aLee et al, -c, 2000b. The use of the simplest effective corrections in a planar study introduces a degree of complexity that rivals that of a full PET study.…”
Section: Choice Of Imaging Modality For Biodistribution Studiesmentioning
confidence: 99%
“…Kang and Katsaggelos have shown that it is possible to simultaneously estimate an image and its degree of regularization by making an explicit dependence between them [12]. The simultaneous estimation is obtained by finding the minimum of (6) under the constraint of a linear relationship between the regularization parameter and the regularizing functional (7) By so doing, is made proportional to and , which both increase with the noise in the data. The value of can be set such that the function is monotonically increasing, mapping into and such that the functional is convex with a unique minimum.…”
Section: Theorymentioning
confidence: 99%
“…Attenuation correction can thus be performed, which is essential to the quantification of SPECT studies [4]- [6]. Iterative algorithms are compulsory for reconstructing images from SPECT data with the aim of quantification using attenuation correction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation is responsible for large biases with underestimation of the distribution values as large as 80% in cardiac SPECT, independently of the size of the structure [2]. Attenuation correction is thus required for quantification purpose rather than resolution recovery.…”
Section: B Diffusion Regularization and Approximate Inversionmentioning
confidence: 99%